At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

If f(x) = 2x-4 and g(x) = x2 - 4x, find g(-4) And the (x2 - 4x) the 2 is a exponent

Sagot :

Evaluate the given function in x=-4.

This is, replace the x in the function for -4 and find the value of g(-4).

[tex]\begin{gathered} g(x)=x^2-4x \\ g(-4)=(-4)^2-4(-4) \\ g(-4)=16+16 \\ g(-4)=32 \end{gathered}[/tex]

The value of g(-4) is 32.